2007
DOI: 10.1007/s11695-007-9068-4
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Disease among Obese Patients in Taiwan

Abstract: Cholelithiasis in Asian obese patients is significantly associated with increased diastolic blood pressure and hepatitis B surface antigen carriers. Because chronic liver disease seems to be a risk factor for cholelithiasis in both non-obese and obese populations, prophylactic cholecystectomy can be considered in obese patients with HBsAg positivity. We did not find evidence that H. pylori has a role in the pathogenesis of gallbladder disease and gallstone by histologic and serologic examinations. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
0
30
0
4
Order By: Relevance
“…A prospective study by Sheen and Liaw [20] showed a linear trend toward the prevalence of cholecystolithiasis increased with the progression of liver disease, i.e., from "healthy" HBsAg carrier through chronic hepatitis to liver cirrhosis. Chronic hepatitis B seems to be a risk factor for gallbladder disease [28]. Paradoxically, chronic hepatitis B was not a risk factor in the development of NASH [21] and HBsAg-positive subjects had less prevalence of metabolic syndrome than HBsAgnegative subjects [32].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A prospective study by Sheen and Liaw [20] showed a linear trend toward the prevalence of cholecystolithiasis increased with the progression of liver disease, i.e., from "healthy" HBsAg carrier through chronic hepatitis to liver cirrhosis. Chronic hepatitis B seems to be a risk factor for gallbladder disease [28]. Paradoxically, chronic hepatitis B was not a risk factor in the development of NASH [21] and HBsAg-positive subjects had less prevalence of metabolic syndrome than HBsAgnegative subjects [32].…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of NASH and gallbladder disease was 33.8% [21] and 10.1% [28], respectively, among obese population in Asia. In this study, we first compared the clinical risk factors between NASH and gallbladder disease among morbid obesity that had fatty liver disease undergoing bariatric surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover the Systolic BP was also greater than 130 in 55.30%. Reason being people with hypertension may have more sympathetic nerve activities that may probably decrease bowel movements [31].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that cholelithiasis in Asian obese patients is significantly associated with increased diastolic blood pressure. It is possible that people with hypertension may have more sympathetic nerve activities that easily inhibit bowel movement and cause GSD [18]. …”
Section: Discussionmentioning
confidence: 99%